2016
DOI: 10.5430/ijba.v8n1p22
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Organisational Citizenship Behaviour through the Lens of Age

Abstract: This paper sheds light on the mechanisms through which age diversity climate affects employees' positive attitudes and behaviours. Specifically, the study examines: a) the mediating role of affective commitment in the relationship between age diversity climate and organisational citizenship behaviour, and b) the moderating effect of employees' focus on future occupational opportunities on the link between age diversity climate and affective commitment. Applying regression analyses to a sample of 326 employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 70 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…Similarly, Seligman and Csikszentmihalyi () argue that future mindedness is beneficial for well‐being, because it is a positive individual difference characteristic that can act as a buffer against mental illness and improve quality of life. Building upon this line of reasoning, primary studies have found generally positive associations between OFTP and the constructs of job satisfaction (e.g., Weikamp & Göritz, ), organizational commitment (e.g., Profili, Sammarra, & Innocenti, ), work engagement (e.g., Schmitt, Zacher, & de Lange, ), continuance intentions (e.g., Chen, ), achievement motivation (e.g., Froehlich et al, ), and motivation to learn (Kochoian, Raemdonck, Coertjens, Frenay, & Beausaert, ). Additionally, negative relationships have been found between OFTP and emotional exhaustion (e.g., Barbieri et al, ) and intentions to retire (e.g., Bal, de Lange, et al, ).…”
Section: Outcomes Of Oftpmentioning
confidence: 98%
“…Similarly, Seligman and Csikszentmihalyi () argue that future mindedness is beneficial for well‐being, because it is a positive individual difference characteristic that can act as a buffer against mental illness and improve quality of life. Building upon this line of reasoning, primary studies have found generally positive associations between OFTP and the constructs of job satisfaction (e.g., Weikamp & Göritz, ), organizational commitment (e.g., Profili, Sammarra, & Innocenti, ), work engagement (e.g., Schmitt, Zacher, & de Lange, ), continuance intentions (e.g., Chen, ), achievement motivation (e.g., Froehlich et al, ), and motivation to learn (Kochoian, Raemdonck, Coertjens, Frenay, & Beausaert, ). Additionally, negative relationships have been found between OFTP and emotional exhaustion (e.g., Barbieri et al, ) and intentions to retire (e.g., Bal, de Lange, et al, ).…”
Section: Outcomes Of Oftpmentioning
confidence: 98%
“…Within the workplace, diversity refers to those visible (e.g., age, gender) or invisible (e.g., sexual orientation) characteristics of employees that can either be a resource or an obstacle to the achievement of today’s organizational goals of competitiveness and performance [ 3 , 4 ]. Accumulating research in the field of age at work indicate that a potential obstacle stemming from increased age diversity within the workplace is the rise of age prejudice and age discrimination [ 1 , 5 , 6 , 7 , 8 ]. In fact, research supports that the emergence of positive or negative effects of diversity largely depends on the workplace practices that encourage or devalue certain personal characteristics (e.g., age) [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by social exchange theory [ 19 , 20 ], a high-diversity climate is also likely to promote employees’ perceptions of being cared for by their organization, regardless of age [ 18 ]. As a result, employees will be willing to reciprocate through increased trust, higher performance and organizational citizenship behaviors, and reduced turnover [ 8 , 14 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations